Total Electron Content Variations During an HSS/SIR‐Driven Geomagnetic Storm at High and Mid Latitudes - Geethakumari, G. P.; Aikio, A. T.; Cai, L.; Vanhamäki, H.; Virtanen, I. I.; Coster, A.; Marchaudon, A.; Blelly, P.‐L.; Maute, A.; Norberg, J.; Oyama, S.; Zhang, Y.; et al. (John Wiley & Sons, 2025)
Two interacting high‐speed solar wind streams (HSSs) and associated stream interaction regions (SIR) caused a moderate geomagnetic storm during 14–20 March 2016. The spatio‐temporal evolution of the total electron content (TEC) during the storm is studied by using Global Navigation Satellite System (GNSS) data. The moderate storm caused significant and long‐lasting changes on TEC within the polar cap (70°–90° MLAT), at auroral and sub‐auroral latitudes (60°–70° MLAT), and at mid‐latitudes (40°–60° MLAT). A 25%–50% depletion in TEC was observed for six days in the day, dusk and dawn sectors in the polar cap region and in the day and dusk sectors at the auroral and sub‐auroral latitudes. Sub‐auroral polarization streams observed by the Defense Meteorological Satellite Program satellite contributed to the sub‐auroral dusk TEC decreases. At mid‐latitudes, TEC depletion was observed in all local time sectors 21 hr after the storm onset. It is suggested that ion‐neutral frictional heating causes the TEC depletions, which is further supported by the observed spatial correlation between TEC depletions and ∑O/N2 decreases at mid‐latitudes observed by TIMED/GUVI. The storm induced a prolonged positive phase at mid‐latitudeslasting 9 hr. In the polar cap, enhancements of TEC up to 200% were caused by polar cap patches. TEC increases were the dominant feature in the night and morning sectors within the auroral oval because of particle precipitation and resulted up to regionally averaged 6 TECU (200%) increases.